Telltale Signs of Idiopathic Intracranial Hypertension With Normal Opening Cerebrospinal Fluid Pressure. (January 2023) - Foska, Aikaterini; Palaiodimou, Lina; Stefanou, Maria Ioanna; Alonistiotis, Dimitrios; Bakola, Eleni; Papagiannopoulou, Georgia; Arvaniti, Chrysa; Bonakis, Anastasios; Lachanis, Stefanos; Tsivgoulis, Georgios
Introduction: Idiopathic Intracranial Hypertension (IIH) with normal opening cerebrospinal fluid (CSF) pressure comprises a rare IIH variant. Case Report: We report the case of a non-obese Caucasian woman, who presented with asymmetrical papilledema, typical IIH-findings on optic nerve sonography and brain magnetic resonance imaging (MRI), and was diagnosed with IIH despite normal opening CSF pressure. Following treatment with acetazolamide, a complete remission of her symptoms was achieved, accompanied by significant improvement of the fundoscopy findings. Conclusion: Although normal opening CSF pressure in IIH patients is rare, clinicians should be aware of this IIH variant and promptly indicate IIH treatment in patients presenting with typical clinical symptoms and neuroimaging findings suggestive of IIH.